(untitled) (Handbook of Treatment Algorithms for Medical and Pharmacy Students, 2025)
Author Mr. Sreedhar Sumalapu, Head of the Department, Department of Pharmacy Practice, Nirmala College of Pharmacy (Autonomous), Kadapa, Andhra Pradesh, India Abstract Psychiatric treatment algorithms are guideline-based, measurement-informed, and highly individualized, with a dual focus on symptom remission and functional recovery. The algorithm for Major Depressive Disorder (MDD) is a stepwise approach, beginning with first-line psychotherapy (e.g., CBT) or pharmacotherapy (e.g., SSRI/SNRI). Failure of an adequate trial (6-8 weeks) triggers a subsequent step, such as switching to a different agent or augmenting with a second medication (e.g., bupropion, aripiprazole). The algorithm for anxiety disorders (e.g., GAD) is similar, prioritizing CBT, SSRIs, or SNRIs, with agents like buspirone or pregabalin as second-line or adjunctive options; benzodiazepines are reserved for short-term, acute management. The algorithm for schizophrenia is stratified by treatment response. First-line therapy is a second-generation antipsychotic (SGA). Treatment resistance, defined by failure of two different antipsychotic trials, is a specific indication to advance the algorithm to clozapine. The algorithm for bipolar disorder is bifurcated by the patient's acute state. Mania is managed with mood stabilizers (e.g., lithium, valproate) or SGAs, whereas bipolar depression is treated with agents with specific efficacy for this phase (e.g., lurasidone, quetiapine), strictly avoiding antidepressant monotherapy. Keywords: Psychiatric Algorithms, Major Depressive Disorder, Anxiety Disorders, Schizophrenia, Bipolar Disorder, Pharmacotherapy VIEW PDF